First-year Accounting students’ confidence levels during Covid-19: Evidence over a period of two years at a South African university - Papageorgiou, E.; Viviers, H.; De Villiers, R. (South African Journal of Higher Education, 2023)
The Coronavirus Disease (Covid-19) outbreak has caused serious and continuous concerns globally within the higher education sector. One of these is the confidence levels of students to perform specific academic-related tasks. This study explored first-year accounting students’ confidence levels during Covid-19 over a two-year period at a South African university to determine if any associations exist between students’ gender, age, choice of study, language, and method of study funding, compared to confidence level, whilst applying a quantitative research design. Mixed results were obtained. Areas for further research identified include collaboration with other universities, and to expand the scope of the population, to determine the status of students’ confidence levels for different accountancy-related modules during and post-Covid-19. The study will inform and sensitise lecturers, students and academic institutions regarding the confidence levels of students to perform specific academic-related tasks within accounting education and training under Covid-19 conditions.